Evaluación del crecimiento y supervivencia de Dipteryx charapilla (J.F. Macbr.) Ducke de la plantación n° 19 del CIEFOR – Puerto Almendra, Loreto – Perú. 2021 - Carrasco Cenepo, Jenrry (2023)
The objective of the study was to determine the growth in height and diameters of the plants and their survival of the plants. The evaluations were carried out in a Dipteryx charapilla plantation (Plot No. 19) in CIEFOR – Puerto Almendra. The average increase in diameter of the plants was 0.06 cm and the increase in height was 2.94 cm. Plant survival varies between 30% to 65%, while mortality reached 70%. The largest number of plants presented GOOD quality with 55 seedlings, which represents 27.64% of the total seedlings evaluated, followed by REGULAR quality with 27 living individuals, which indicates 13.57% and, finally, the least number of individuals were observed in BAD quality with 4 seedlings that represented 2.01% of the total. At a general level in the experiment, the Good quality was recorded (band 2, 4, 5, 6, 7, 9 and 10). It is necessary to carry out similar studies with other native forest species in CIEFOR - Puerto Almendra.